Study of energy storage and electrocaloric behavior of lead-free Fe-doped BCT ceramics. Issue 1 (9th December 2020) - Redhu, Preeti; Hooda, Ashima; Sharma, Preeti; Dahiya, Sajjan; Punia, Rajesh; Tandon, R. P.
Abstract: The present study investigates energy storage and electrocaloric properties of lead-free barium calcium titanate (BCT) ceramics with compositions B0.80 Ca0.20 Ti1–3x/4 Fex O3 ( x = 0.000, 0.005, 0.010, 0.015, and 0.020) prepared by solid-state reaction route. Variation of polarization with the temperature at various applied fields has been used to study the electrocaloric behavior of the prepared ceramic samples. An indirect method based on the thermodynamic Maxwell's relation is employed to evaluate adiabatic temperature change (Δ T ), isothermal entropy change (Δ S ), and electrocaloric responsivity (Δ T /Δ E ). Energy storage density ( Wrec ), energy loss density ( Wloss ), and efficiency (η) of Fe-doped BCT ceramics have been obtained from the integral area of ferroelectric hysteresis loops. With an increase in Fe content, room temperature energy storage density is observed to increase from 87.26 mJ/cm 3 to 140.18 mJ/cm 3 . A relatively high energy storage efficiency of η = 51% has been achieved at electric field ̴ 10 kV/cm for x = 0.020. Also, an appreciable increase in energy storage density with field and temperature has been observed. These studies suggest application of prepared ceramic compositions for new generation cooling or heating devices and dielectric materials with high energy storage density.